All Days 2014
DOI: 10.2118/168581-ms
|View full text |Cite
|
Sign up to set email alerts
|

Fully-Coupled Numerical Evaluations of Multiwell Completion Schemes: The Critical Role of In-Situ Pressure Changes and Well Configuration

Abstract: The development of many shale plays has been met with significant challenges, including low production rates and rapid production declines, and many ideas and concepts have been tried to address these. Multi-well completions, like ‘Simulfracs’ and ‘Zipper fracs’ for example, have been attempted as a means to increase production, but these have met with only limited success. The authors have shown in previous work that multi-well completions increase the in-situ stress field around the created hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…The simulation results illustrate that the zipper fracturing has only a modest impact on the activation of natural fractures, but strong risk of screenout. Nagel et al (2014) extended the previous work by considering the effect of changing natural fractures pressure and concluded that the improvement in well stimulation using different completion strategies such as zipper fracturing is highly dependent on in-situ pore pressure, in-situ stress, natural fracture mechanical properties, natural fracture orientation, and initial aperture.…”
Section: Zipper Fracturingmentioning
confidence: 64%
See 1 more Smart Citation
“…The simulation results illustrate that the zipper fracturing has only a modest impact on the activation of natural fractures, but strong risk of screenout. Nagel et al (2014) extended the previous work by considering the effect of changing natural fractures pressure and concluded that the improvement in well stimulation using different completion strategies such as zipper fracturing is highly dependent on in-situ pore pressure, in-situ stress, natural fracture mechanical properties, natural fracture orientation, and initial aperture.…”
Section: Zipper Fracturingmentioning
confidence: 64%
“…Therefore, in an effort to increase the operational efficiency of hydraulic fracturing and reduce cost, several multiwell completion schemes, such as zipper fracturing and Љsimul-fracturing,Љ have been introduced. However, the productivity and return on investment from such fracturing schemes have seen mixed results (Nagel et al 2014). It is important, however, to account for various techniques to come up with the optimized completion technique.…”
Section: Introductionmentioning
confidence: 99%
“…The simulation results illustrate that the zipper fracs only have modest impact on the natural fractures activation but strong risk to screenout. Nagel et al 2014 extended the previous work by considering the effect of changing natural fractures pressure and states that the improvement in well stimulation using different completion strategies such as zipper fracturing is highly dependent on in-situ pore pressure, in-situ stress, natural fracture mechanical properties, natural fracture orientation, and initial aperture.…”
Section: Zipper Fracturingmentioning
confidence: 79%
“…In an effort to increase the operational efficiency of hydraulic fracturing and reduce cost, several multiwell completion schemes, such as zipper fracturing and Љsimul-fracturingЉ, have been introduced but with mixed results (Nagel et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al 2011;Daniels et al 2007;Le Calvez et al 2007;Nagel et al 2013Nagel et al , 2014. Although the complex fracture network provides key channels for gas flow, it also brings new challenges for shale gas development plan, which contains optimizing hydraulic fracture design and well productivity prediction.…”
Section: Introductionmentioning
confidence: 99%